The Effect of Intrathecal 20 mg Ketamine on 0.5% 15 mg Bupivacaine in Spinal Anesthesia For Lower Extremity Surgery - Chandra, Nopial Ade; Hamdi, Tasrif; Lubis, Andriamuri Primaputra (Journal of Anaesthesia and Pain, 2026)
Background: Regional anesthesia is widely used in orthopedic procedures to reduce complications such as nausea, vomiting, and pulmonary aspiration. Intrathecal ketamine is known to prolong analgesia duration, but evidence remains limited. This study aimed to compare the effectiveness and side effects of combining intrathecal ketamine 20 mg with 0.5% bupivacaine 15 mg versus bupivacaine alone in spinal anesthesia for lower extremity surgery. Methods: A randomized controlled trial (RCT) was conducted at RS Haji Medan and Rumkit Tk II Putri Hijau Medan, involving 30 patients undergoing spinal anesthesia. Subjects were divided into two groups: Group A (Ketamine + Bupivacaine) and Group B (Bupivacaine only). Variables observed included onset and duration of sensory and motor blockade, sedation level, hemodynamic responses, and adverse effects. Data were analyzed using SPSS v24.0. Results: No significant differences were found in baseline characteristics between the two groups. The addition of ketamine did not significantly affect the onset or duration of sensory and motor blockade. Hemodynamic parameters such as heart rate and blood pressure remained stable in both groups. However, sedation levels were lower and the incidence of adverse effects (such as nausea, shivering, and hallucinations) was higher in the ketamine group. Conclusion: The addition of intrathecal ketamine 20 mg to bupivacaine 0.5% 15 mg slightly prolonged spinal anesthesia but was associated with an increased risk of adverse effects and lower sedation. This combination should be used cautiously in clinical practice.